Antibacterial nylon composite material and application thereof

By adding special antibacterial agents to automotive nylon materials, a polymer with quaternary ammonium salt and silver ions in the molecular chain is formed, which solves the problem of insufficient antibacterial performance of existing automotive nylon materials, and achieves the effect of improving antibacterial properties and maintaining mechanical properties.

CN119823564AActive Publication Date: 2025-04-15SUZHOU RUNJIA ENGINEER PLASTIC
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411744290.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-30
Publication Date
2025-04-15
Estimated Expiration
2044-11-30

AI Technical Summary

Technical Problem

The existing nylon materials for automobiles have shortcomings in antibacterial properties, which are difficult to meet the need to increase the importance of health.

Method used

An antibacterial nylon composite material is used, which includes nylon, glass fiber, toughener, silane coupling agent and an antibacterial agent composed of silver lactate, 1,3,5 triazine-2,4,6-triacyl chloride and dodecylmethyldihydroxyethylammonium chloride. Antibacterial agents are prepared through specific reaction steps to form polymers with quaternary ammonium salt groups and silver ions in the molecular chain, improving antibacterial properties.

Benefits of technology

It improves the antibacterial properties of nylon materials, while maintaining good mechanical properties, meets the requirements for nylon materials in the automotive field, and provides a solid foundation for the long-term development of the automotive field.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119823564A_ABST
    Figure CN119823564A_ABST
Patent Text Reader

Abstract

The invention relates to an antibacterial nylon composite material and application thereof, and belongs to the technical field of high polymer materials. Silver lactate reacts with 1, 3, 5-triazine-2, 4, 6-triacyl chloride to obtain silver lactate modified 1, 3, 5-triazine-2, 4, 6-triacyl chloride, then the silver lactate modified 1, 3, 5-triazine-2, 4, 6-triacyl chloride reacts with dodecyl methyl dihydroxyethyl ammonium chloride to form a polymer with quaternary ammonium salt groups and silver ions in molecular chains, the polymer has quaternary ammonium salt and silver ion antibacterial groups at the same time, the quaternary ammonium salt and silver ion antibacterial groups play a synergistic effect, and the antibacterial property of the polymer is improved. The antibacterial performance can be improved. The nylon material disclosed by the invention has good antibacterial property and good mechanical property, and meets the use requirements on polymer materials such as nylon and the like in the current automobile field.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an antibacterial nylon composite material and application thereof, belonging to the technical field of polymer materials. Background Art

[0002] Nylon has excellent mechanical properties, electrical properties, heat resistance, toughness, oil resistance, wear resistance, self-lubrication and chemical resistance, and has been widely used in various fields. With the rapid development of automobile miniaturization, greening and high performance of electronic and electrical equipment, nylon is widely used in the automotive field as the main structural material. In addition, in recent years, with the rapid development of new energy vehicles, the application of nylon in new energy batteries, connectors, charging devices and other components has also increased rapidly. For example, PA66 nylon-based composite materials have been used in automobile engine hoods, intake manifolds, fuel tank linings, distributors and decorative parts.

[0003] In order to better meet the needs of the development of the automotive industry, relevant scholars and experts have proposed that the future development trend of automotive nylon materials is to increase the fluidity, heat resistance, high pressure tracking resistance, halogen-free flame retardancy and other properties of nylon materials. However, for automotive interior parts, in addition to the strength and toughness of the material, as people pay more attention to health, the antibacterial property of the material has also received more and more attention.

[0004] Therefore, there is an urgent need to develop an antibacterial nylon composite material for automobiles. Summary of the invention

[0005] The purpose of the present invention is to provide an antibacterial nylon composite material to meet the requirements of antibacterial performance of nylon materials for automobiles.

[0006] Another object of the present invention is to provide an antibacterial nylon composite material for use as a nylon material for automobiles, so as to improve the antibacterial properties of the nylon material for automobiles.

[0007] The invention provides an antibacterial nylon composite material, comprising the following components in parts by mass: 50-70 parts of nylon, 26-36 parts of glass fiber, 7-12 parts of a toughening agent, 0.2-0.6 parts of a silane coupling agent, and 1.5-3 parts of an antibacterial agent; the antibacterial agent is prepared by a method comprising the following steps: mixing silver lactate and 1,3,5-triazine-2,4,6-trichloride, and then mixing the product after the mixed reaction with dodecylmethyldihydroxyethylammonium chloride to obtain the antibacterial agent; the molar ratio of 1,3,5-triazine-2,4,6-trichloride, silver lactate and dodecylmethyldihydroxyethylammonium chloride is 1:1:1.

[0008] Preferably, the preparation method of the antibacterial agent is as follows: a dichloromethane solution of 1,3,5-triazine-2,4,6-trichloride with a mass fraction of 5% to 10% is added dropwise to a dichloromethane solution of silver lactate with a mass fraction of 0.5% to 2%, and then mixed and reacted at 25 to 30° C. for 2 to 4 hours, and then a dichloromethane solution of dodecylmethyldihydroxyethylammonium chloride is added to the reacted system, the temperature is raised to 30 to 35° C., the mixing reaction is continued for 15 to 30 hours, and the antibacterial agent is obtained after impurities are removed.

[0009] Preferably, the mass fraction of dodecylmethyldihydroxyethylammonium chloride in the dichloromethane solution of dodecylmethyldihydroxyethylammonium chloride is 15% to 25%.

[0010] Preferably, the impurity removal method is as follows: filtering the system after the mixed reaction, and then evaporating the filtrate to dryness.

[0011] Preferably, the nylon is PA6.

[0012] Preferably, the toughening agent is maleic anhydride grafted polyethylene or EPDM rubber compounds.

[0013] Preferably, the silane coupling agent is an epoxy silane coupling agent.

[0014] Preferably, the silane coupling agent is γ-(2,3-glycidoxy)propyltrimethoxysilane.

[0015] The present invention provides an application of the antibacterial nylon composite material as a nylon material for automobiles.

[0016] The beneficial effects of the present invention are as follows:

[0017] (1) The present invention uses silver lactate and 1,3,5-triazine-2,4,6-trichloride to react to obtain silver lactate-modified 1,3,5-triazine-2,4,6-trichloride, which is then reacted with dodecylmethyldihydroxyethylammonium chloride to form a polymer having quaternary ammonium salt groups and silver ions in the molecular chain. The polymer has both quaternary ammonium salt and silver ion antibacterial groups, and the two play a synergistic role to improve the antibacterial performance.

[0018] (2) The present invention uses a polymer containing a large number of nitrogen atoms in the molecular chain as the antibacterial agent carrier polymer, which can improve the affinity between the antibacterial agent and nylon, improve the intermolecular micro-force between the antibacterial agent and nylon, and then improve the dispersion uniformity of the antibacterial agent in the polymer nylon, thereby improving the antibacterial performance.

[0019] (3) The present invention uses silane coupling agent to improve the bonding strength between antibacterial agent and other additives and nylon molecular chain, improve the dispersion uniformity and stability of the additives, and ensure the long-term stability of nylon material performance.

[0020] (4) In addition to having good antibacterial properties, the nylon material of the present invention also has good mechanical properties, which meets the current automotive requirements for the use of polymer materials such as nylon, and provides a solid foundation for the long-term development of the automotive field. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 Schematic diagram of the tensile strength of the antibacterial nylon composite material of each embodiment of the present invention and the comparative example;

[0022] Figure 2 It is a schematic diagram of the elongation at break of the antibacterial nylon composite material of each embodiment of the present invention and the comparative example;

[0023] Figure 3 It is a schematic diagram of the simply supported beam notched impact strength of the antibacterial nylon composite materials of various embodiments of the present invention and comparative examples;

[0024] Figure 4 Schematic diagram of the antibacterial rate of the antibacterial nylon composite materials of various embodiments and comparative examples of the present invention against Escherichia coli and Staphylococcus aureus. DETAILED DESCRIPTION

[0025] The following examples are intended to further illustrate the present invention rather than to limit the scope of protection of the present invention.

[0026] Example 1

[0027] The antibacterial nylon composite material of this embodiment includes the following components in parts by weight: 50 parts of nylon, 26 parts of glass fiber, 8 parts of toughening agent, 0.2 parts of silane coupling agent, and 1.5 parts of antibacterial agent. Among them, the nylon is commercially available PA6, the toughening agent is maleic anhydride grafted polyethylene, and the silane coupling agent is γ-(2,3-epoxypropoxy)propyltrimethoxysilane. The antibacterial agent is prepared by a method comprising the following steps: fully dissolving silver lactate in dichloromethane to obtain a silver lactate solution with a mass fraction of 0.5%, then dripping a dichloromethane solution of 1,3,5-triazine-2,4,6-trichloride with a mass fraction of 5% into the silver lactate solution at 25°C (the molar ratio of 1,3,5-triazine-2,4,6-trichloride to silver lactate is 1:1), then adding triethylamine acid binding agent, stirring and reacting for 4 hours, then adding a dichloromethane solution of dodecylmethyldihydroxyethylammonium chloride (the mass fraction of dodecylmethyldihydroxyethylammonium chloride in the dichloromethane solution of dodecylmethyldihydroxyethylammonium chloride is 25%, and the molar ratio of dodecylmethyldihydroxyethylammonium chloride to 1,3,5-triazine-2,4,6-trichloride is 1:1), heating to 35°C, continuing to stir and react for 15 hours, filtering, evaporating the filtrate to dryness, and obtaining the antibacterial agent. Among them, the structural formula of dodecyl methyl dihydroxyethyl ammonium chloride is as follows:

[0028]

[0029] Example 2

[0030] The antibacterial nylon composite material of this embodiment includes the following components in parts by mass: 70 parts of nylon, 36 parts of glass fiber, 12 parts of toughening agent, 0.6 parts of silane coupling agent, and 3 parts of antibacterial agent. Among them, the nylon is commercially available PA6, the toughening agent is an EPDM rubber compound, and the silane coupling agent is γ-(2,3-epoxypropoxy)propyltrimethoxysilane. The antibacterial agent is prepared by a method comprising the following steps: fully dissolving silver lactate in dichloromethane to obtain a silver lactate solution with a mass fraction of 2%, then dripping a dichloromethane solution of 1,3,5-triazine-2,4,6-trichloride with a mass fraction of 10% into the silver lactate solution at 30°C (the molar ratio of 1,3,5-triazine-2,4,6-trichloride to silver lactate is 1:1), then adding triethylamine acid binding agent, stirring and reacting for 2 hours, then adding a dichloromethane solution of dodecylmethyldihydroxyethylammonium chloride (the mass fraction of dodecylmethyldihydroxyethylammonium chloride in the dichloromethane solution of dodecylmethyldihydroxyethylammonium chloride is 15%, and the molar ratio of dodecylmethyldihydroxyethylammonium chloride to 1,3,5-triazine-2,4,6-trichloride is 1:1), heating to 30°C, continuing to stir and react for 30 hours, filtering, evaporating the filtrate to dryness, and obtaining the antibacterial agent. Among them, the structural formula of dodecyl methyl dihydroxyethyl ammonium chloride is as follows:

[0031]

[0032] Example 3

[0033] The antibacterial nylon composite material of this embodiment includes the following components in parts by weight: 60 parts of nylon, 30 parts of glass fiber, 7 parts of toughening agent, 0.4 parts of silane coupling agent, and 2 parts of antibacterial agent. Among them, the nylon is commercially available PA6, the toughening agent is maleic anhydride grafted polyethylene, and the silane coupling agent is γ-(2,3-epoxypropoxy)propyltrimethoxysilane. The antibacterial agent is prepared by a method comprising the following steps: fully dissolving silver lactate in dichloromethane to obtain a silver lactate solution with a mass fraction of 1%, then dripping a dichloromethane solution of 1,3,5-triazine-2,4,6-trichloride with a mass fraction of 7% into the silver lactate solution at 28°C (the molar ratio of 1,3,5-triazine-2,4,6-trichloride to silver lactate is 1:1), then adding triethylamine acid binding agent, stirring and reacting for 3 hours, then adding a dichloromethane solution of dodecylmethyldihydroxyethylammonium chloride (the mass fraction of dodecylmethyldihydroxyethylammonium chloride in the dichloromethane solution of dodecylmethyldihydroxyethylammonium chloride is 18%, and the molar ratio of dodecylmethyldihydroxyethylammonium chloride to 1,3,5-triazine-2,4,6-trichloride is 1:1), heating to 32°C, continuing to stir and react for 19 hours, filtering, evaporating the filtrate to dryness, and obtaining the antibacterial agent. Among them, the structural formula of dodecyl methyl dihydroxyethyl ammonium chloride is as follows:

[0034]

[0035] Comparative Example 1

[0036] The antibacterial nylon composite material of this comparative example is different from the antibacterial nylon composite material of Example 1 only in that the antibacterial agent used in the antibacterial nylon composite material of this comparative example is silver lactate.

[0037] Comparative Example 2

[0038] The difference between the antibacterial nylon composite material of this comparative example and the antibacterial nylon composite material of Example 1 is that the antibacterial agent used in the antibacterial nylon composite material of this comparative example is prepared by a method comprising the following steps: fully dissolving silver lactate in dichloromethane to obtain a silver lactate solution with a mass fraction of 0.5%, then adding a dichloromethane solution of 5% trimesoyl chloride by mass to the silver lactate solution at 25°C (the molar ratio of trimesoyl chloride to silver lactate is 1:1), then adding triethylamine acid binding agent, stirring and reacting for 4 hours, then adding a dichloromethane solution of dodecylmethyldihydroxyethylammonium chloride (the mass fraction of dodecylmethyldihydroxyethylammonium chloride in the dichloromethane solution of dodecylmethyldihydroxyethylammonium chloride is 25%, and the molar ratio of dodecylmethyldihydroxyethylammonium chloride to trimesoyl chloride is 1:1), heating to 35°C, continuing to stir and react for 15 hours, filtering, and evaporating the filtrate to dryness to obtain an antibacterial agent. Among them, the structural formula of dodecyl methyl dihydroxyethyl ammonium chloride is as follows:

[0039]

[0040] Comparative Example 3

[0041] The antibacterial nylon composite material of this comparative example is different from the antibacterial nylon composite material of Example 1 only in that the antibacterial agent used in the antibacterial nylon composite material of this comparative example is prepared by a method comprising the following steps: fully dissolving silver lactate in dichloromethane to obtain a silver lactate solution with a mass fraction of 0.5%, and then adding a dichloromethane solution of 1,3,5-triazine-2,4,6-trichloride with a mass fraction of 5% to the silver lactate solution at 25°C (the molar ratio of 1,3,5-triazine-2,4,6-trichloride to silver lactate is 1:3), and then adding triethylamine acid binding agent, stirring the reaction for 4 hours, filtering, and evaporating the filtrate to dryness to obtain the antibacterial agent.

[0042] Comparative Example 4

[0043] The difference between the antibacterial nylon composite material of this comparative example and the antibacterial nylon composite material of Example 1 is that the antibacterial agent used in the antibacterial nylon composite material of this comparative example is prepared by a method comprising the following steps: at 25°C, a 5% dichloromethane solution of 1,3,5-triazine-2,4,6-triacyl chloride is added dropwise to a dichloromethane solution of dodecylmethyldihydroxyethylammonium chloride (the mass fraction of dodecylmethyldihydroxyethylammonium chloride in the dichloromethane solution of dodecylmethyldihydroxyethylammonium chloride is 25%, and the molar ratio of dodecylmethyldihydroxyethylammonium chloride to 1,3,5-triazine-2,4,6-triacyl chloride is 3:2), and then triethylamine acid binding agent is added, the reaction is stirred for 20 hours, filtered, and the filtrate is evaporated to dryness to obtain the antibacterial agent. Among them, the structural formula of dodecylmethyldihydroxyethylammonium chloride is as follows:

[0044]

[0045] Application Examples

[0046] According to the composition ratio of the antibacterial nylon composite material of each embodiment and comparative example, each raw material was added into a twin-screw extruder, melt-extruded at 255°C to obtain an antibacterial nylon composite material, and then the tensile strength, elongation at break, simply supported beam notched impact strength and antibacterial property tests were performed. The test results are shown in Tables 1 and Figure 1-4 shown. Figure 1 is a schematic diagram of the tensile strength of the antibacterial nylon composite material of each embodiment and comparative example, Figure 2 is a schematic diagram of the elongation at break of the antibacterial nylon composite material of each embodiment and comparative example, Figure 3 is a schematic diagram of the simply supported beam notched impact strength of the antibacterial nylon composite material of each embodiment and comparative example, Figure 4The figure is a schematic diagram of the antibacterial rate of the antibacterial nylon composite material of each embodiment and comparative example against Escherichia coli and Staphylococcus aureus. The tensile strength is tested according to the provisions of standard ISO527, the elongation at break is tested according to the provisions of standard ISO527-2, the simply supported beam notched impact strength is tested according to the provisions of standard ISO179-1, and the antibacterial rate is tested according to the provisions of standard QB / T2591-2003, and the strains used in the test are Escherichia coli and Staphylococcus aureus.

[0047] Table 1 Tensile strength, elongation at break, simply supported beam notched impact strength and antibacterial properties of the antibacterial nylon materials of each embodiment and comparative example

[0048]

[0049] From Table 1, Figure 1-4 It can be seen that the antibacterial nylon composite material of the present invention can make the nylon material have high strength, high elongation at break and high antibacterial ability by selecting appropriate toughening agents, silane coupling agents and antibacterial agents, which can meet the needs of the automotive field.

Claims

1. An antibacterial nylon composite material, characterized in that: The invention comprises the following components in parts by weight: 50-70 parts of nylon, 26-36 parts of glass fiber, 7-12 parts of toughening agent, 0.2-0.6 parts of silane coupling agent and 1.5-3 parts of antibacterial agent; the antibacterial agent is prepared by a method comprising the following steps: silver lactate and 1,3,5-triazine-2,4,6-trichloride are mixed and reacted, and then the product after the mixed reaction is further mixed and reacted with dodecylmethyldihydroxyethylammonium chloride to obtain the antibacterial agent; the molar ratio of 1,3,5-triazine-2,4,6-trichloride, silver lactate and dodecylmethyldihydroxyethylammonium chloride is 1:1:

1.

2. The antibacterial nylon composite material according to claim 1, characterized in that: The preparation method of the antibacterial agent is as follows: a dichloromethane solution of 1,3,5-triazine-2,4,6-triacyl chloride with a mass fraction of 5% to 10% is added dropwise to a dichloromethane solution of silver lactate with a mass fraction of 0.5% to 2%, and then mixed and reacted at 25 to 30° C. for 2 to 4 hours, and then a dichloromethane solution of dodecylmethyldihydroxyethylammonium chloride is added to the system after the reaction, and the temperature is raised to 30 to 35° C., and the mixing reaction is continued for 15 to 30 hours, and the antibacterial agent is obtained after impurities are removed.

3. The antibacterial nylon composite material according to claim 2, characterized in that: In the dichloromethane solution of dodecylmethyldihydroxyethylammonium chloride, the mass fraction of dodecylmethyldihydroxyethylammonium chloride is 15% to 25%.

4. The antibacterial nylon composite material according to claim 2, characterized in that: The method of removing impurities is as follows: the system after the mixed reaction is filtered, and the filtrate is evaporated to dryness.

5. The antibacterial nylon composite material according to any one of claims 1 to 4, characterized in that: The nylon is PA6.

6. The antibacterial nylon composite material according to any one of claims 1 to 4, characterized in that: The toughening agent is maleic anhydride grafted polyethylene or EPDM rubber compounds.

7. The antibacterial nylon composite material according to any one of claims 1 to 4, characterized in that: The silane coupling agent is an epoxy silane coupling agent.

8. The antibacterial nylon composite material according to claim 7, characterized in that: The silane coupling agent is γ-(2,3-epoxypropoxy)propyltrimethoxysilane.

9. Use of the antibacterial nylon composite material according to any one of claims 1 to 8 as a nylon material for automobiles.

Citation Information

Patent Citations

  • Antibacterial composition containing organic silver complexes, antibacterial treatment methods using the same and antibacterial formed article

    CN101437400A

  • Preparation method of low-volume-shrinkage antibacterial dental resin composite material

    CN104887535A

  • Composite material for dental prosthesis and preparation method of composite material

    CN105232340A